SEDIMENDT CHARACTERISTICS OF COASTAL WATERS AROUND INTENSIVE SHRIMP PONDS DURING WET SEASON IN PUNDUH BAY, PESAWARAN DISTRICT OF LAMPUNG PROVINCE - Mudian Paena; Rezki Antoni Suhaimi; Muhammad Chaidir Undu (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
The study was conducted using survey method. The sampling points were based on the distances from pond outlet toward offshore which were 25, 100, 200, 400, 800, 1600 and 3200 m. Sample of sediments were collected using sediment grab then about 1-1.5 kg of samples were stored in plastic bags for analysis of pH, redox potential, carbon organic. The in-situ measurements were conducted for pH and redox potential using a pH mV and pH meter, probe HANNA instruments HI 8424, whereas other sediment quality variables were analysed under laboratory. The results of this study showed that the pH sediments were ranged between 6.38 – 7.80 with average of 7.36. Redox potential of sediments ranged between -186 to 72 mV, average - 88.39 mV. Carbon organic ranged between 0.30 – 9.85%, average 3.09%. Organic matter ranged between 0.30 – 9.85%, average 3.16%. Total nitrogen were ranged between 0.05 – 0.25% with average of 0.17%, phosphate were 8.62 – 187.71 mg/L with average of 88.43 mg/L. Based on the sediment characteristics, the sediments of Punduh Bay had been polluted by organic matters. Keywords: sediment characteristics, shrimp ponds, Punduh bay,                             Pesawaran district, Lampung province